2011
DOI: 10.1039/c1an15509a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behaviour and voltammetric sensitivity at arrays of nanoscale interfaces between immiscible liquids

Abstract: Arrays of nanoscale interfaces between immiscible electrolyte solutions were formed using silicon nitride nanopore array membranes. Nanopores in the range from 75 nm radius down to 17 nm radius were used to form the nano-interfaces. It was found that the liquid organic phase electrolyte solution filled the pores so that inlaid nano-interfaces were formed with the aqueous phase. Cyclic voltammetry at these nano-interface arrays demonstrated steady-state behaviour at the larger interfaces but the voltammetric wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 42 publications
8
55
0
Order By: Relevance
“…Each membrane contained 400 pores in a hexagonal close-packed arrangement with pore centre-to-centre separations, , of 20-times the pore radius, ( ). Scanning electron microscopy (SEM) micrographs of these nanopore arrays have been reported previously [11,15,38].…”
Section: Preparation Of Nano-interface Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…Each membrane contained 400 pores in a hexagonal close-packed arrangement with pore centre-to-centre separations, , of 20-times the pore radius, ( ). Scanning electron microscopy (SEM) micrographs of these nanopore arrays have been reported previously [11,15,38].…”
Section: Preparation Of Nano-interface Arraysmentioning
confidence: 99%
“…NanoITIES can offer benefits comparable to those experienced at nanoelectrode arrays, such as enhanced mass transport (due to radial diffusion), decreased charging current and decreased impact of solution resistance [11,16]. NanoITIES studies reported by Rimboud et al [15], Liu et al [4] and Shao and Mirkin [7] focussed on ion sensing using cyclic voltammetry as a technique. However, there is little information published on the chronoamperometric response at nano-interface arrays [13] despite numerous studies reporting the chronoamperometric response at microelectrochemical devices, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A B [43] copyright 2011 Royal Society of Chemistry, from Analyst, 2011, 136, 4674, [40] copyright 2011 Royal Society of Chemistry, respectively).…”
Section: Experimental Systemsmentioning
confidence: 99%
“…This approach allowed the determination of structural properties of the nanopores, including their density, shape and size, and provided a basis for understanding the permeability of nanoporous membranes. In addition, arrays of nano-ITIES were developed for the investigation of electrochemical behaviour and detection of ions such as TEA + , [36,40] tetrapropylammonium (TPrA + ) [37a, 41] and protonated propranolol. [42] These nanoITIES arrays were formed by placing nanoporous membranes, such as silicon nitride perforated with EBL-patterned nanopores, at the interface.…”
Section: Experimental Systemsmentioning
confidence: 99%